Antibacterial activity of white tea extract against gram positive and negative bacteria - Asri Widyasanti; Siti Hajar; Dadan Rohdiana (Jurnal Penelitian Teh dan Kina, 2015)
This research was carried out to deterÂmine antibacterial activity of white tea extract against gram positive and gram negative bacteria based on its MIC (minimum inhibitory concentration). Ethanol solution 96% were used to extract of white tea with a ratio of 1:9 (w/v) by using maceration method. Paper disc diffusion method was used to determination of the MIC. The concentrations were used of 2%, 4%, 6%, 8%, 10%, and 12% (w/v). The results of this research showed that MIC of white tea extract of 4%, 6%, 6% and 10% (w/v) against Pseudomonas aeruginosa ATCC 9027, StaphyÂlococcus aureus ATCC 29213, Staphylococcus epidermidis ATCC 12228, and Escherichia coli ATCC 25922, respectively. The inhibition zone for 4 bacteria were 10.83 mm, 10.08 mm, 10.16 mm and 12.08 mm respectively. This result of research concluded that white tea extract have antibacterial activity against both gram positive and gram negative bacteria